A handful of dogs : with four phonics stories - Rae, Elspeth, 1973-; Rae, Rowena (Rae, Elspeth, 1973- Meg and Greg, 2024)
"This is the fifth book in the phonics-based, decodable Meg and Greg series for beginning or striving readers. Includes illustrations and worksheets."--